Analisis Eksistensi Perpustakan Sebagai Penyedia Informasi DI UPT Perpustakaan Daerah Tulungagung Pada Era New Normal - Aditya Rahmawati Syarifudin; Prisca Budi Juvitasari (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
The development of technology makes information very needed as well as the library which can be categorized as a gathering place for information. However, due to the Covid-19 pandemic, the library's performance is not optimal. The purpose of the study was to determine the existence of libraries in the new normal era and the strategies used by librarians in maintaining their existence and increasing interest in visiting the Tulungagung Regional Library. The researcher used descriptive qualitative method. The informants used in this study were the head of the library, librarians, and users. The results showed that the existence of the Tulungagung Regional Library was quite good even though there were still shortcomings because the procurement of books had decreased. However, the library also opens an ebook application service and an online storytelling program for children called DoReMi in collaboration with several institutions. The condition of the library building is also still lacking, but the role of the librarian is quite good. Interest in visiting the library has also decreased, but public enthusiasm for visiting the library remains high. The strategies taken by librarians are not many, they are only able to adapt, implement and maximize existing services, create an online storytelling program for children called DoReMi and ebook applications, enforce improvised regulations and intensify online promotions and outreach to the public. This is because the Tulungagung Regional Library is still hindered by government regulations.